Private Higher Education Intention in Adopting Blockchain Technology on Accounting Information System (AIS) (Public Accounting and Sustainability, 2024)
Research aims: This study was conducted with the aim of testing and obtaining empirical evidence regarding the intention of private higher education institutions (HEIs) to adopt blockchain in accounting information systems (AIS) using the unified theory of acceptance and use of technology (UTAUT) model. Design/Methodology/Approach: The sample of this research is private HEIs in Java that have been accredited "Very Good" and "Excellent," and the respondents representing the sample of this research are the head of private HEIs in the finance sector, and the head of the financial agency/institution/bureau of private HEIs selected through purposive sampling technique. Data were collected using a questionnaire and analyzed using the Partial Least Square method. Research findings: The results indicate that performance expectancy, effort expectancy, and social influence have a positive impact on the intention of private HEIs to use blockchain in AIS. Theoretical contribution/Originality: This research provides a theoretical contribution by confirming the UTAUT theory and expanding the literature related to the adoption of blockchain in AIS in private HEIs. Practitioner/Policy implication: The findings of this research can serve as a basis for policy-making regarding the implementation of blockchain technology in the private HEIs education sector and offer valuable insights for private HEIs to prepare for the implementation of blockchain technology in AIS in the education sector. Research limitation/Implication: The sample was limited to private higher education in Java, making the results not generalizable to a broader context.